What International Students Think about US Higher Education - Chow, Patricia (International Higher Education, 2011)
Key Words: prospective international students, perceptions of U.S. higher education, global student mobility. This article discusses the attitudes and perceptions that international students have of U.S. higher education, based on results from surveys conducted by the Institute of International Education (IIE) in eleven key places of origin. Despite not having any national policies designed to attract students from other countries, the U.S. remains well-positioned in the international student marketplace, with various pull factors attracting students to the U.S., including the high quality and diverse range of U.S. higher education institutions, and the perception that the U.S. is a welcoming country for international students. However, anti-push factors also exist, with cost predominating and perceptions of visa difficulties persisting in some countries.